If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(k + -4) = 12 Reorder the terms: 9(-4 + k) = 12 (-4 * 9 + k * 9) = 12 (-36 + 9k) = 12 Solving -36 + 9k = 12 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 9k = 12 + 36 Combine like terms: -36 + 36 = 0 0 + 9k = 12 + 36 9k = 12 + 36 Combine like terms: 12 + 36 = 48 9k = 48 Divide each side by '9'. k = 5.333333333 Simplifying k = 5.333333333
| 58=-y+179 | | -11x+4+8x-4+3x=0 | | -3x-21=-81 | | -11x+4+8x-4+3x=o | | 5g+7g-4= | | 35x-7y=491 | | 2x+54=2(x+28) | | 4(2x+3)+8=2(X+3)+4 | | -2x-22=-54 | | x+x=270 | | 3(X-5)+25=3X+10 | | 0.5x=0.2+75 | | X+4(2)=3 | | R+r+r+r+r=0 | | cosx^2=1 | | 0.3333x+14=40 | | 4(y-3)+9-3y=0 | | 0=-5X+-2X | | k-7.6=10.35 | | 0.5x^2=4y | | 0.333x+14=40 | | 15x^5+3x^4-40x^3-8x^2-15x-3=0 | | a-25=15 | | C=b-bx-5 | | 18x+2y=34 | | -8+5(g+2)=0 | | 2+0.54t=50 | | -6(4y)-7+2(7y+4)= | | 8(x-6)-5=4(x-4) | | -2x+17=9 | | 98-0.54t=50 | | 0.5(4x-16)-(-6)=-12 |